2020
DOI: 10.1007/s11845-020-02339-8
|View full text |Cite
|
Sign up to set email alerts
|

Thickness of epicardial and pericoronary adipose tissue measured using 128-slice MSCT as predictors for risk of significant coronary artery diseases

Abstract: Aim Determination the relationship between the epicardial adipose tissue thickness (EATT) and pericoronary adipose tissue thickness (PATT) and the risk of significant coronary artery diseases (CAD) using the coronary artery calcium score (CACS). Materials and methods The study group consisted of 80 patients. The risk of significant CAD was estimated based on CACS. Adipose tissue thickness was measured based on multiplanar reformation (MPR), left ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Demircelik et al 7 also found that the calcium score was higher in the obstructive group. In accordance with Gać et al 26 and Rosito et al, 27 we found a significant association between the calcium score and CT-measured EAT and PCFT.…”
Section: Discussionsupporting
confidence: 92%
“…Demircelik et al 7 also found that the calcium score was higher in the obstructive group. In accordance with Gać et al 26 and Rosito et al, 27 we found a significant association between the calcium score and CT-measured EAT and PCFT.…”
Section: Discussionsupporting
confidence: 92%
“…Some reports are in line with our results, Xie et al [12] described that EAT thickness was higher in CAD and significantly increased during progression of CAD severity. In a study conducted by Gać et al [13], it was indicated that positive correlation was noted between significant CAD, EAT thickness and PCFT in 80 suspected patients by coronary CT angiography. Other studies had similar results as our data regarding correlation of EAT thickness and PCFT and obstructive CAD [14,15].…”
Section: Discussionmentioning
confidence: 94%
“…CCTA is a cross-sectional method that enables examination of the vascular lumen, vessel wall, and surrounding tissue in addition to the lumen. 15) CCS is considered a good marker of coronary atherosclerosis. 16) CCS provides an overall evaluation of atherosclerosis by measuring the degree of coronary calcification present in atherosclerotic plaques and reflecting the lifetime cumulative influence of risk factors as well as inherited and environmental markers.…”
Section: Discussionmentioning
confidence: 99%